The Implementation of the Core Values of “AKHLAK” and their Impact on Service Quality at PT. Taspen Cirebon - Nesha Lavenia; Ipik Permana (CV. Media Digital Publikasi Indonesia, 2026)
The role of state-owned enterprises (SOEs) in public service is quite complex. This is because, in addition to pursuing profitability, SOEs are also required to provide high-quality services to the public. To support efforts to ensure quality public service, the Ministry of State-Owned Enterprises issued Circular Letter No. SE-7/MBU/07/2020 in 2020 regarding the Core Values of SOE Human Resources. The objective of this study is to explore the implementation of these values in depth and analyze their implications for service quality. The research methodology is descriptive qualitative, utilizing data triangulation from observation, interviews, and documentation. The “AKHLAK” values are implemented into employees’ daily work; for instance, the value of Integrity is demonstrated by employees through high precision and caution when calculating pension benefits and claims, the value of Competence is applied by allocating budgets from headquarters to conduct employee training and education, the value of Harmony is realized through the principle of equality, the value of Loyalty is manifested in compliance with regulations, the value of Adaptability is realized through the digitization of services, and the value of Collaboration is realized through establishing cooperation with various parties. The conclusion drawn is that the “AKHLAK” values have comprehensive implications for the five dimensions of service quality in the SERVQUAL model by Zeithaml et al. Each “AKHLAK” value does not stand alone but is interconnected and reinforces one another in creating quality service.